“Leading without a map”: The impact of non-managerial academic heads on educational leadership - Tangente Jr., Sanny L. (UIN Raden Mas Said Surakarta, 2025)
This study investigated the leadership of academic heads who assume leadership roles without formal training or backgrounds in management. This study addresses this gap by exploring how such individuals navigate the demands of academic leadership within a private educational institution in the Philippines. Using a qualitative case study approach, the research focused on three academic heads from various departments in a single private school who lacked formal managerial education or training. Data were gathered through in-depth interviews and thematic analysis was employed to capture their lived experiences. The findings of the study revealed the following: (1) performance in the academic management were leading with passionate desire, obedience to the protocol, and tapping the people; (2) perceived challenges and coping mechanisms were learning the strategies on teaching-learning through trainings, countering the teachers’ limitations through further education and professional development, and eradicating self-doubt with prayer and constant communication; (3) relationship to the faculty and staff were through open communication, recognition, and collaboration; (4) leadership styles and strategies were trust and communication, laissez-faire, and treating the faculty with inherent value; (5) ways in adapting to the changing educational landscape were enhanced flexibility and collaboration. The findings of this study contributed to the understanding of the complexities and challenges faced by academic heads with non-managerial educational backgrounds as they navigate their way into academic management.